Effects of Du Meridian Electroacupuncture Combined with Treadmill Training on Motor Function of Rats with Spinal Cord Injury - CHENG Mei; TIAN Yu; PENG Jing; YU Shuangqi; ZHANG Xuejun; DING Fan (康复学报)
ObjectiveTo explore the effects and underlying mechanism of Du meridian electroacupuncture combined with treadmill training on motor function of rats with spinal cord injury (SCI).MethodsA total of 50 healthy female SPF-grade SD rats were randomly divided into sham operation group, model group, treadmill group, electroacupuncture group and treadmill+electroacupuncture group, with 10 rats in each group. In the sham group, the T10 laminectomy was performed without SCI; while in the other four groups, Allen's method and New York University (NYU) spinal cord injury impactor method were used to establish T10 SCI model. Rats with death or BBB motor function scale score>2 were excluded, and finally eight rats were included in each group. The sham operation group and the model group had free diet and activities without any intervention. The treadmill group received treadmill training, once a day, 30 minutes a time, five days a week for four weeks. The electroacupuncture group received electroacupuncture stimulation at Dazhui (DU14) and Mingmen (GV4), once a day, 20 minutes a time, five times a week for four weeks. The treadmill+electroacupuncture group received treadmill training followed by electroacupuncture stimulation, and the training methods were the same as those of the treadmill group and the electroacupuncture group. Before and after the operation, BBB scale was used to evaluate the recovery of motor function after SCI. After operation, magnetic resonance imaging (MRI) was used to detect the recovery of the SCI segment; immunohistochemistry was used to detect the protein expression levels of brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF); Western blot was used to detect the protein expression levels of postsynaptic density-95 (PSD-95) and SynapsinⅠ.Results(1) BBB score: compared with the model group at the same time, BBB scores of the treadmill group, the electroacupuncture group and the treadmill+electroacupuncture group increased significantly at 2, 3, 4 weeks after operation, and the differences were statistically significant (P<0.05). Compared with the treadmill group and the electroacupuncture group at the same time, BBB score of the treadmill+electroacupuncture group increased significantly at 3, 4 weeks after operation, and the differences were statistically significant (P<0.05). (2) Recovery of the SCI segment: compared with the model group, the spinal cord tissues in the treadmill group and the electroacupuncture group recovered significantly, and the inflammatory reaction area was reduced. Compared with the model group, the treadmill group and the electroacupuncture group, the treadmill+electroacupuncture group showed more complete spinal cord structure, smaller injury range, lower MRI hyperintensity, and less inflammatory reaction. (3) Protein expression levels of BDNF and NGF: compared with the sham operation group, the model group, the treadmill group and the electroacupuncture group, the protein expression level of BDNF in the treadmill+electroacupuncture group was significantly higher (P<0.05). Compared with the model group, the protein expression level of NGF in the treadmill+electroacupuncture group increased significantly (P<0.05). (4) Protein expression levels of PSD-95 and SynapsinⅠ: compared with the sham operation group, the protein expression levels of PSD-95 and SynapsinⅠ in the model group and the electroacupuncture group decreased significantly (P<0.05), the protein expression levels of PSD-95 and SynapsinⅠ in the treadmill group and the treadmill+electroacupuncture group increased significantly (P<0.05). Compared with the model group, the protein expression levels of PSD-95 and SynapsinⅠ in the treadmill group and the treadmill+electroacupuncture group increased significantly (P<0.05), and the protein expression level of PSD-95 in the electroacupuncture group decreased significantly (P<0.05), while the protein expression level of SynapsinⅠ increased significantly (P<0.05). Compared with the treadmill group, the protein expression levels of PSD-95 and SynapsinⅠ in the electroacupuncture group decreased significantly (P<0.05), and the protein expression levels of PSD-95 and SynapsinⅠ in the treadmill+electroacupuncture group increased significantly (P<0.05). Compared with the electroacupuncture group, the protein expression levels of PSD-95 and SynapsinⅠ in the treadmill+electroacupuncture group increased significantly (P<0.05).ConclusionDu meridian electroacupuncture combined with treadmill training can effectively improve the spinal cord injury and motor function of SCI rats, possibly by regulating the protein expression levels of BDNF, NGF, PSD-95 and SynapsinⅠ.